Sensitivity-based approach for evaluation and enhancement of available transfer capability using FACTS devices - Sureban, Manjula S.; Ankaliki, Shekappa G. (Institute of Advanced Engineering and Science, 2025)
Available transfer capability (ATC) plays an important role in the reliable and secure power system operation. It measures the transfer capability available in the transmission system for further trading over and above existing commitments without violating the system limits. The increased demand for electric power in recent years due to increasing population, automation in industries, and use of electricity in transportation, and also the deregulation of power systems results in an overload of the transmission network and hence congestion in the system. Therefore, quick and accurate calculation of ATC and its enhancement is needed for secured and reliable operation. It is possible to enhance ATC by placing the flexible alternating current transmission systems (FACTS) devices of appropriate size and at optimal locations in the system. In this paper, a computationally efficient sensitivity-based approach for evaluation and enhancement of available transfer capability in the presence of of FACTS devices is presented. The developed approach is implemented on the IEEE 14 bus system.